Global burden and cross-country inequalities in gallbladder and biliary tract cancer (1990–2021) with projections to 2050: insights from the global burden of disease study 2021 - Xie, Diya; Liu, Fengmin; Zhou, Daosen; Zhu, Qiang; Xiao, Fangting; Zhang, Kun (Frontiers in Medicine, 2025)
BackgroundGallbladder and biliary tract cancer (GBTC) presents a worldwide health challenge with a poor prognosis. Previous studies indicated an escalating burden and potential health inequalities, necessitating an updated investigation.MethodsThis study utilized data from the Global Burden of Disease (GBD) study, covering 204 countries from 1990 to 2021. Joinpoint regression evaluated temporal trends in age-standardized incidence rates (ASIR) and age-standardized disability-adjusted life years rates (ASDR) for GBTC. The Bayesian age-period-cohort (BAPC) model projected disease burden up to 2050. Inequality analysis assessed disparities by genders across countries, and decomposition analysis determined the contributions of demographic and epidemiological factors.ResultsFrom 1990 to 2021, the incident cases of GBTC increased from 107,797 to 216,768, while Disability-Adjusted Life Years (DALYs) rose from 2,326,089 years to 3,732,121. Joinpoint regression analysis revealed a global decrease in ASIR (AAPC = −0.39, 95% CI: −0.49 to −0.28) and ASDR (AAPC = −0.97, 95% CI: −1.07 to −0.88). Gender disparities were notable, with a polar reversal observed: females exhibited consistently higher ASDR levels across three decades, although both ASDR and ASIR showed continuous decreases. In contrast, males experienced a decreased ASDR but increased ASIR, with both metrics eventually surpassing those of females. The projection model also suggested diverging ASIR trends between genders. Cross-country inequality analysis revealed persistent disparities, where higher SDI countries continue to bear a greater burden, and global improvement in health equity for males remains insufficient. Decomposition analysis indicated that population growth and ageing were primary drivers of disease burden increase, whereas epidemiological changes contributed to a reduction, particularly in higher SDI quintiles.ConclusionDespite improvements, GBTC burden is still greater in high SDI regions compared to lower SDI areas, contrary to expectations. Unexpected polar reversal of gender differences warrants further attention.